1999
DOI: 10.1016/s0025-3227(98)00182-0
|View full text |Cite
|
Sign up to set email alerts
|

East Asian monsoon climate during the Late Pleistocene: high-resolution sediment records from the South China Sea

Abstract: Based on the study of 10 sediment cores and 40 core-top samples from the South China Sea (SCS) we obtained proxy records of past changes in East Asian monsoon climate on millennial to bidecadal time scales over the last 220,000 years. Climate proxies such as global sea level, estimates of paleotemperature, salinity, and nutrients in surface water, ventilation of deep water, paleowind strength, freshwater lids, fluvial and=or eolian sediment supply, and sediment winnowing on the sea floor were derived from plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
445
2
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 723 publications
(514 citation statements)
references
References 107 publications
43
445
2
2
Order By: Relevance
“…A similar interpretation may apply to a large set of published and unpublished planktic data from sediment traps and core tops in ocean regions as different as the northern and equatorial Atlantic [e.g., Simstich, 1998;Deuser et al, 1981aDeuser et al, , 1981bGanssen, 1983], the Arabian Sea, and South China Sea [Wang et al, 1999]. Overall, the spatial distribution patterns of these data suggest that d 13 C values of various planktic foraminifera species primarily reflect the nutrient concentrations in ocean surface water ambient to shell calcification, besides various secondary forcings such as air-sea exchange of CO 2 , sea surface temperature, secular d 13 C variations, and vital and metabolic effects.…”
Section: Tracers Of Nutrient Concentration and Bottom Water Ventilationmentioning
confidence: 67%
“…A similar interpretation may apply to a large set of published and unpublished planktic data from sediment traps and core tops in ocean regions as different as the northern and equatorial Atlantic [e.g., Simstich, 1998;Deuser et al, 1981aDeuser et al, , 1981bGanssen, 1983], the Arabian Sea, and South China Sea [Wang et al, 1999]. Overall, the spatial distribution patterns of these data suggest that d 13 C values of various planktic foraminifera species primarily reflect the nutrient concentrations in ocean surface water ambient to shell calcification, besides various secondary forcings such as air-sea exchange of CO 2 , sea surface temperature, secular d 13 C variations, and vital and metabolic effects.…”
Section: Tracers Of Nutrient Concentration and Bottom Water Ventilationmentioning
confidence: 67%
“…It may also be used to explain the close relationship between the H. guttatus populations of these two river systems. There were several ice ages and inter-ice ages and their associated sea-level changes in the northeastern part of the South China Sea during the Quaternary (Wang et al, 1999;Liu et al, 2003). The Hanjiang River System and the Jiulongjiang River System are geographically very close to each other (Fig.…”
Section: Relationships Among Hemibagrus Guttatus Of the Pearl Hanjiamentioning
confidence: 97%
“…All these results indicated that there was no significant difference between the North River, the East River and the tributaries of the West River, at least for H. guttatus populations. The similarity among populations of these three rivers might be explained by their possible confluence during several large ice ages in the Pleistocene when sea-level was low (Wang et al, 1999;Liu et al, 2003). Floods might have also created temporary freshwater connections between these rivers, especially between the West River and the North River, which may have facilitated the exchange of H. guttatus populations.…”
Section: Relationships Among Hemibagrus Guttatus Of the West River Nmentioning
confidence: 99%
See 1 more Smart Citation
“…There is convincing evidence that HL deposition was accompanied by the formation of a freshwater lid , which possibly stopped or strongly reduced North Atlantic deep water (NADW) formation and thermohaline circulation (Broecker, 1994;Paillard and Labeyrie, 1994;Maslin et al, 1995;Vidal et al, 1997;Zahn et al, 1997). The signature of Heinrich events has been found not only in North Atlantic sediments (e.g., the Arabian and South China seas; Schulz et al, 1998;Wang et al, 1999) but also in terrestrial records (e.g., Grimm et al, 1993;Lowell et al, 1995;Benson et al, 1996;Sanchez-Goñi et al, 2000) and has been correlated with the Greenland ice core isotope record , pointing to possible teleconnections between high-and low-latitude climates on short time scales.…”
Section: Introductionmentioning
confidence: 99%